A Look at an Automation Adoption Through a Human Performance Technology Lens: A Case Study of Bank Tellers and Automated Teller Machines. Issue 2 (10th February 2021) - Mavers, Scott; Baker, Rose
Abstract: This case study tells the story of the influence of automation introduced by the adoption of the automated teller machine on the performance of bank tellers through a human performance technology lens. The performance improvement opportunities for bank tellers are reviewed using automation theory, definitions, and models. Detailed in the case is how this change in the process, practice, and value of bank teller performance can be expressed through primary alignment focus, worthy performance, and leisure.